Training for career development : a case study in Percetakan Nasional (M) Berhad - Abu Safian, Adnan (Universiti Malaysia Sarawak (UNIMAS), 2004)
The topic for this study is Training For Career Development: A Case Study In Percetakan Nasional (M) Berhad (PNMB). The main purpose is to study the perception of employees towards training and career development programs organized by PNMB. \ This study is essential for PNMB' rder to identify the important factors and elements that are useful for the management to plan and design effective training programs for the employees. The identification of the training needs is crn ial for the organization to avoid organizing irrelevant training programs, which are not required by the employees. Without reliable training design, the organization would not achieve the training objectvies, and likewise the participants would not produce the expected outcomes after the aining. This study If'lculd also identify how the employees perceived the importance of training to the career development and how far they elieve that training experience is one of the important factors for promotion and recognition. It also tries to identify the important area of training that should be improvise by the management in order to get the better outcomes and effects to the organization's productivity and effectiveness. In this study, few definitions, theories, and reviews from the past researchers and theorist are quoted, as supporting information. While, the primary data and the secondary data were collected in order to support the hypotheses and for the analysis. The primary data was obtained through the questionnaires that were distributed by using stratified and sample random sampling where the target groups were PNMB's employees in different groups, class of occupation, gender, qualification, and different section or unit. The secondary data wa ob . ned from articles, annual reports and company's official doc The data from the questionnaires were analyzed by using the Statistical Package of Social Science (SPSS), and Microsoft Excel program. The data were tested using Chi-Square, and Kaiser-Meyer-Olkin (KMO) Test, while the mean of the variables has been analyzed to determine the significant. Itbn be concluded that the majority of the employees were positive towards training programs organized by PNMB and believed that it was useful for their career development.